Granulation of the autochthonous planktonic bacterial community of seawater for saline wastewater treatment. Issue 7 (10th June 2020) - Sarvajith, M.; Nancharaiah, Y. V.
Abstract : Aerobic granular sludge was cultivated from the halophilic bacterial community of seawater. This strategy utilized autochthonous bacteria for effectively removing nitrogen and phosphate from saline wastewaters. Abstract : Aerobic granular sludge (AGS) process is a fast-growing sustainable biological treatment for wastewater. Activated sludge (AS) is the standard inoculum used for cultivating AGS, even for the treatment of saline wastewaters. However, the application of the allochthonous AS community for both developing halotolerant AGS and establishing biological nutrient removal (BNR) under saline conditions is a challenging task. To circumvent this problem, herein, the cultivation of AGS directly from the autochthonous planktonic bacterial community of seawater was investigated. For developing halophilic AGS, a sequencing batch reactor was operated by directly supplying nutrient-amended seawater without inoculum ( i.e., AS or AGS). The approach described herein succeeded in rapidly granulating the planktonic bacteria of seawater and establishing BNR at a 34 ppt salinity. The ammonium and total nitrogen removals of 92–100% and 81–90% were observed during 22–100 days of start-up, respectively. Interestingly, nitrite accumulation was not observed under saline conditions. Phosphate removal progressively improved and stabilized at over 76% within 2 months of start-up. The phosphate removal profiles comprised of P release and uptake phases, which are typical to those of the enhanced biological phosphorus removal mechanism. The granulation of planktonic microbes involved distinct events such as the formation of micro-aggregates, macro-aggregates, and granules but not flocs. Granular growth was observed within few days, suggesting that the granulation of the autochthonous planktonic microbial community of seawater is a rapid phenomenon. The granules were dense (1.5 g ml −1 ) and compact (SVI5 : 6 ml g −1 ) and had an excellent settling velocity (41.2 m h −1 ) on day 25. Moreover, 16S rRNA gene sequencing revealed that AGS had lesser bacterial diversity than the seawater microbiome due to the enrichment of α-proteobacteria. The removal of nitrogen and phosphorus was not significantly impacted at the lower salinities of 25 and 17 ppt. Furthermore, the halophilic AGS was able to achieve an efficient BNR and treatment of real seafood processing wastewater without acclimation. Thus, granulation of the autochthonous halophilic bacteria of seawater is a novel strategy for developing halophilic AGS and to achieve a high BNR under saline conditions.